The Availability of Critical Thinking Skills in the Arabic Language and Islamic Education Textbooks of the Third Grade Depending on their Teachers’ Point View in Jerash - Zubeidat, Walid Falah Zaeed; Bani Ahmad, Odeh Mustafa (Journal of Islamic and Religious Studies, 2022)
This study aimed at investigating the availability of critical thinking skills in the Arabic language and Islamic education textbooks depending on their teachers’ point of view in Jerash Governorate. The researchers have used the functional analytical approach. They prepared a questionnaire that consisted of 36 paragraphs which have targeted four skills, and the sample consisted of 97 female teachers. After finding the arithmetic mean and the standard deviation of the four skills, the results revealed that the targeted skills are highly present in the Arabic language and Islamic education textbooks according to their teachers’ point of view. Accordingly, the researchers recommended conducting more studies that investigate critical thinking, and training the teachers to teach it, as well as to involve teachers in the process of composing school textbooks.